Productivity and technical characteristics of fiber and yarn of the strains and cultivars of the upland and perennial cottons in the northeast. (1989 and 1990 harvests) - Santana, João Cecilio Farias; da Costa, Joaquim Nunes; Freire, Elêusio Curvelo; de Andrade, Francisco Pereira; de Gusmão, João Laurênio; Almeida, Maria Gorete de Macedo; Lima, Maria do Socorro Nogueira (Pesquisa Agropecuaria Brasileira, 1994)
The productivity and physical characteristics of the fiber and yarn of six strains and three cultivars of upland cotton, five cultivars, one hybrid, and eleven strains of perennial cotton of precocious cycle, three cultivars and six strains of late cycle perennial cotton were studied. Of the 35 materials in test, 30 were developed by Genetics Breeding specialists of the Centro Nacional de Pesquisa de Algodão (CNPA) and five by other research institutes of the country. The analysis or test of upland cotton were conducted in Surubim, PE, Brazil, in 1989 and 1990, and in Souza, PB, Brazil, in 1989, and those of the perennial cotton, in Patos, PB, in 1989 and 1990. The herbaceous strains possess fibers of commercial length varying from 30 to 32 mm. or 34 to 36 mm., and the uniformity of length of the fiber varying from 51.7 to 54.4% weak fiber resistance and from average to strong single strand yarn tenacity. Strains of perennial cotton CNPA-3 BB and CNPA 86-9SR F predominate with yields of cotton seeds above 1,105 kg/ha, long fibers (34 to 36 mm) and strong resistance of 8.4 lb/mg. The strains and cultivars of late cycle perennial cotton possess extra long fibers (36 to 38 mm.), especially CNPA 85-1 FBL (Sm2F) and CNPA 85-3 BFL (Sm2FL) strains, with commercial lengths of 38 to 40 mm., strong breaking point of a single strand of yarn, and index superior to 15.0 gf/tex, in spite of low average productivity of 208 kg./ha of this type of cotton.